Forensic Reporting Process of Injured Cases as a Result of Security Forces Intervention to Protest Demonstrations Case Series - Koçar, İlker and Koçyatağı, Ökkeş and Kar, Hakan and Bilgin, Nursel Gamsız and Dokgöz, Halis (The Bulletin of Legal Medicine, 2015)
Many injuries, even deaths can be seen as a result of the intervention of the security forces to protest demonstration or social events in our country. The right of individual application to medical facilities for their health status and treatment is ensured by constitutional law and international legal regulations. Despite this assurance many problems can occur during forensic reporting process concerned with both medical facilities and judicial authorities. Key words: Social event; Protest demonstration; Injury; Individual application Forensic report.